The structure of a membrane adenylyl cyclase bound to an activated stimulatory G protein - Chao Qi; Simona Sorrentino; Ohad Medalia; Volodymyr M. Korkhov (2019)
The architecture of a signaling hub Adenylyl cyclases (ACs) respond to a variety of inputs to generate the signaling molecule cyclic adenosine monophosphate. ACs are regulated by G proteins, which are activated by upstream receptors. Qi et al. determined the structure of bovine membrane AC9 bound to an activated G protein αs subunit by cryo–electron microscopy at 3.4-angstrom resolution. The structure provides the full architecture of AC9, including a helical domain that connects the transmembrane and catalytic domains. The model reveals how the domains interact to regulate enzymatic activity, including suggesting a mechanism of self-inhibition. Science , this issue p. 389